2006
DOI: 10.1007/s10582-006-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved optical and electrical characteristics of capillary underwater discharges

Abstract: Dynamic characteristics of an AC driven capillary discharge produced in a water solution were studied by means of a fast digitizing oscilloscope and a multi-channel photon counter with a nanosecond time resolution. Typical current and voltage traces, together with emission intensities produced by several electronically excited species, were recorded for initial solution conductivities in the range of 100 ÷ 1 000 µS cm −1 . Fast relaxation of the discharge following a breakdown event was observed. Typical time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The OH radical generation is investigated by recording the light emission in the wavelength range 280-400 nm. This part of the discharge spectrum corresponds to the OH radical transition 2) [31,32]. The light intensity I ij due to a transition from the energy state i to energy state j is proportional to the number of radicals in the excited state i, i.e.…”
Section: Kinetics Of Oh Radical Generationmentioning
confidence: 99%
“…The OH radical generation is investigated by recording the light emission in the wavelength range 280-400 nm. This part of the discharge spectrum corresponds to the OH radical transition 2) [31,32]. The light intensity I ij due to a transition from the energy state i to energy state j is proportional to the number of radicals in the excited state i, i.e.…”
Section: Kinetics Of Oh Radical Generationmentioning
confidence: 99%
“…In these so-called underwater electrodeless discharge schemes plasma is generated in one or more holes in a dielectric separating two water vessels. In capillary discharges, the length-to-diameter ratio of the holes is 1 [22][23][24][25][26], whereas it is of the order of 0.1-1 in diaphragm discharges [27][28][29][30][31][32]. Diaphragm discharges have been studied in view of applications such as water 0963-0252/07/020341+14$30.00 © 2007 IOP Publishing Ltd Printed in the UK Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…decontamination [31,33,34], chemical synthesis [15,35,36] and shock wave generation [37]. On capillary underwater discharges, however, only very few reports can be found [22][23][24][25][26]. Recent research by the authors showed that periodic plasma generation in an asymmetrical capillary induces a flow of liquid between the two vessels, which might be utilized to design a micropump [24].…”
Section: Introductionmentioning
confidence: 99%
“…In these so-called underwater 'electrodeless' schemes, plasma is formed inside one or more holes in a dielectric separating two water vessels. In a capillary discharge, the length-to-diameter ratio of the hole(s) is 1 [22][23][24][25][26], whereas it is of the order of 0.1-1 in a diaphragm discharge [27][28][29][30][31][32]. Underwater electrodeless discharges have been studied in connection with water decontamination [31,33,34], chemical synthesis [15,35,36] and shock wave generation [37].…”
Section: Introductionmentioning
confidence: 99%